Acute toxicity test of anthelmintic herbal on Artemia salina larvae - I Ketut Devananda Wicaksana; Kamelia Roiyan; Dinatul Aini; Syauzatta Amani; Widya Wulandari; Muhammad Abdurrahman Fardiaz; Raisya Hasina (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Jamu X is a traditional medicine that is believed to provide anti-inflammatory effects, contains natural ingredients such as Curcuma xanthorrhiza Robx and Curcuma aeruginaosa Robx, has long been used to treat worm infections in children, but it has not passed preclinical tests. The use of traditional medicine in Indonesia has also increased to 44.3%, 55.3% in liquid form, and the rest in powder form. Therefore, this study aimed to determine the potential acute toxicity of Jamu X to Artemia salina larvae presented as its Furthermore, to determine the damaged parts of the larval organs using the Brine Shrimp Lethality Test (BSLT) method. This experimental study used 10000, 1000, 100, 10, 1, and 0.1 ppm, and each concentration contained 10 Artemia salina larvae. Then, we obtained the upper limit of 10,000 and the lower limit of 1000. In the following test, the larvae were grouped into six groups consisting of 10 Artemia salina larvae, and each group was given Jamu